COGNITIVE MECHANISMS IN THE DIDACTICS OF TECHNICAL VOCATIONAL SUBJECTS IN THE LIGHT OF RESEARCH ON BIOELECTRICAL BRAIN ACTIVITY - Prauzner, Tomasz (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The main objective of the paper is to present arguments about the multidimensional character of effectiveness of school education and to discuss a number of factors that influence the outcome of education directly or indirectly. Assessing the effectiveness of school education sheds light on its current problems and indicates directions for future research on innovative approaches to solving such problems. Preliminary assumptions for research based on EEG results concerning cognitive performance during student learning in technical fields will also be presented.